2020
DOI: 10.5944/ried.24.1.27690
|View full text |Cite
|
Sign up to set email alerts
|

E-Guess: Usability Evaluation for Educational Games

Abstract: Usabilidad es un aspecto relevante en el análisis de la interfaz hombre-máquina, ya que se trata del diálogo que se establece entre sujetos, artefacto y calidad de uso e interacción que permite el sistema. Este trabajo presenta una heurística específica para la evaluación de juegos educativos, creada a partir de Game User Experience Satisfaction (GUESS) y, concomitantemente, las herramientas de evaluación de Nielsen. Para ello, se realizó una investigación aplicada con un enfoque cuantitativo-cualitativo - con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As in the previous case, the questions that evaluated the playability parameter showed that the players had good gaming experiences; there was constant empathy among the player, the game and the learning process. The high values obtained in Q8 to Q14 indicate positive percentages, affirming the quality of our game in terms of operating rules, design, dynamics and mechanics. ,, The purposes and explanation of each item that evaluated the playability parameter are shared below (Table ). The percentage listed in the table corresponds to the maximum value in each feature.…”
Section: Validation Of the Strategymentioning
confidence: 55%
See 1 more Smart Citation
“…As in the previous case, the questions that evaluated the playability parameter showed that the players had good gaming experiences; there was constant empathy among the player, the game and the learning process. The high values obtained in Q8 to Q14 indicate positive percentages, affirming the quality of our game in terms of operating rules, design, dynamics and mechanics. ,, The purposes and explanation of each item that evaluated the playability parameter are shared below (Table ). The percentage listed in the table corresponds to the maximum value in each feature.…”
Section: Validation Of the Strategymentioning
confidence: 55%
“…our game in terms of operating rules, design, dynamics and mechanics. 15,38,39 The purposes and explanation of each item that evaluated the playability parameter are shared below (Table 4). The percentage listed in the table corresponds to the maximum value in each feature.…”
Section: 5mentioning
confidence: 99%